Oral exposure to high concentrations of polystyrene microplastics alters the intestinal environment and metabolic outcomes in mice - Hasegawa, Yuka; Okamura, Takuro; Ono, Yuriko; Ichikawa, Takahiro; Saijo, Yuto; Nakanishi, Naoko; Sasano, Ryoichi; Hamaguchi, Masahide; Takano, Hirohisa; Fukui, Michiaki (Frontiers in Immunology, 2024)
IntroductionOral exposure to microplastics (MPs) is a global health concern. In our previous study, MPs induced glucose intolerance and non-alcoholic fatty liver disease (NAFLD) under a high-fat diet-induced leaky gut syndrome (LGS). This study aims to evaluate the effects of high concentrations of MP on lipid metabolism under normal dietary conditions and to assess the changes in the intestinal tract resulting from MP exposure.MethodsC57BL6/J mice were fed a normal diet (ND) without polystyrene MPs (PS-MPs) or with PS-MPs (1000 µg/L or 5000 µg/L) for six weeks. Subsequently, intestinal permeability, gut microbiota, and metabolite levels in the serum, feces, and liver were determined.ResultsMice fed the ND showed no increase in intestinal permeability in either group. However, high MPs concentrations led to increased serum lipid levels and exacerbated fatty liver function. Oral exposure to MPs did not affect the number of innate lymphoid cells or short-chain fatty acids in the intestine. However, it increased the number of natural killer cells, altered the gut microbiota, induced inflammation, and modulated the expression of genes related to nutrient transport in the intestine. The severity of intestinal disturbance tended to worsen with dose.DiscussionDespite the absence of LGS, high concentrations of MPs induced dyslipidemia and NAFLD. Oral exposure to MPs triggered intestinal inflammation via natural killer cells, altered the gut microbiota, and modulated nutrient metabolism. Our study highlights the need for environmental measures to reduce oral MPs exposure in the future.